1991
DOI: 10.1002/ss.37119915407
|View full text |Cite
|
Sign up to set email alerts
|

College‐student survivors of incest and other child sexual abuse

Abstract: This chapter describes the dynamics of childhood sexual abuse, identijies the prevalence of college-student s m l abuse survivors, and addresses the major issues of child sexual abuse as they relate to college students.Since the late 1970s, incest and other forms of child sexual abuse have been a focus of attention for professionals concerned about the well-being of children. Changing laws, significant attention from the media, the creation of sexual abuse prevention programs, and the development of treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
1
0
0
Order By: Relevance
“…These findings support earlier research that found that men and women differed in their rates of sexual victimization but not in their rates of physical victimization (Duane et al, 1997, Sandberg et al, 1987, Worth et al, 1990. The findings that both incest and nonrecent rape survivors were more likely to have experienced physical abuse and that incest survivors were more likely to have experienced nonrecent rape confirm a previous finding (Witchel, 1991) that early violence may place a person at risk for later revictimization. Partial support was also found for the hypothesis that client and counselor characteristics would predict disclosure of interpersonal violence.…”
Section: Discussionsupporting
confidence: 84%
“…These findings support earlier research that found that men and women differed in their rates of sexual victimization but not in their rates of physical victimization (Duane et al, 1997, Sandberg et al, 1987, Worth et al, 1990. The findings that both incest and nonrecent rape survivors were more likely to have experienced physical abuse and that incest survivors were more likely to have experienced nonrecent rape confirm a previous finding (Witchel, 1991) that early violence may place a person at risk for later revictimization. Partial support was also found for the hypothesis that client and counselor characteristics would predict disclosure of interpersonal violence.…”
Section: Discussionsupporting
confidence: 84%